Understanding the Difference Between Autism and the Autistic Spectrum: A Focus on the South African Context - Sithole-Tetani, Ntombophelo (Research in Social Sciences and Technology- OpenED Network, 2024)
Autism is a group of severe developmental disorders with impairments beginning before 30 months of age and characterized by a qualitative disturbance of social development and of language for communication, a stereotyped behaviour, and a lack of a broad set of interests. The expression of autism varies from one individual to the next. It is a communicative disorder and is not due to poor reception. The researchers drew their literature from reputable journal articles, book chapters from established publishers, and informal community conversations amid the researchers’ experiential intuition. Currently, South African children with autism spectrum disorder (ASD) lack government support structures and rely primarily on families for assistance with education and therapy. An additional challenge is that in some South African black communities, autism is not recognized as a disorder. A study exploring differences in the nature, application, experience, and examination of social awareness and understanding of selected educators about new terminology in their environment found that local black teachers had less exposure to autism knowledge, diagnosis, treatment, and prognosis in their communities, and little understanding, awareness, or acceptance of this condition. This article underscores the crucial role of social service professionals, such as psychologists, registered counsellors, social workers, etc, in these communities. Their presence and active involvement provide hope in these challenging times. It recommends that they conduct psychotherapeutic education, which could involve awareness campaigns and counselling about psychotherapeutic education. Their role would be to provide support, guidance, and education to the community members, helping them to build their resilience to fight the coronavirus.